Differences of Horizontal Brushing Method And Combination Method Towards Students' Score Plaque For Class V SDN 22/IV Jambi City - Aida Silfia; Sukarsih Sukarsih; Asio Asio; Aflinda Yenti; Muliadi Muliadi (Jurnal Kesehatan Gigi, 2022)
Problem statement:. This tooth brushing technique consists of several methods that can be used. Its success also depends on the brushing method used. Tooth brushing methods include Bass, Stillman, Fones, Horizontal, Vertical, Roll, and Combination. The behavior of brushing teeth in Jambi Province is 96.4% who brush their teeth every day and 0.69% when brushing their teeth properly.Objectives: 1) To find out the average plaque score for elementary school students who brush their teeth using the horizontal method and the combination method as measured by PHP-M. 2) Knowing the difference between horizontal brushing and the combination method on plaque scores in elementary school students in Jambi City.Method: The method used in this research is to use the waterfall method. The data will be analyzed analytically (bivariate). After getting the data, then the data is tested for normality, when the data is declared more than 0.05 then the Independent T Test is used, which is a type of parametric test to find out whether there is a difference from the estimated value with the value of the statistical calculation.Scientific finding results, and a short conclusion : The obtained significance is 0.000 less than the significant level (α) = 0.05, which means that there is a significant difference between the average plaque scores after the combination method group treatment with the horizontal method. In table t obtained t count -6.119, which means that the average plaque score after the combination method group treatment is lower than the horizontal group.